Development of e-tuition system for UPSR using mastery learning model / Adyaniahadiah Ab. Wahab - Ab. Wahab, Adyaniahadiah (2010)
The use of information and communication technology in education and training has undergone several paradigm shifts over the last three decades. Very recently the notions of e-learning (learning supported by digital electronic tools and media) have emerged. Web-based learning are widely used to support a process of teaching and learning. When compared to CD-ROM learning, the benefits of Web-based learning is stem from the fact that access to the content is easy and requires no distribution of physical materials. In Malaysia, Science subject has been introduced as early as for the students from standard four in primary school. Science subject for primary school students are tested during the Primary School Evaluation Test (UPSR). Unfortunately, there are some students feel that Science is one of the most difficult subject, by using mastery learning model it can help student to improve and achieve a high degree of learning if 2 conditions are met. First condition is each learner must be given sufficient time to master every learning steps in instructional sequence and the second condition is one children must be given remedial help whenever a step is not mastered. Every topic of syllabus is break into unit and all student can learn a set of reasonable objectives with appropriate and sufficient time to learn. Mastery learning puts the techniques of tutoring and individualized instruction into a group learning situation.